Computational Study of Ligand Effects on First-Row Transition Metals - Deckers, Tim (My University, 2012)
This research investigated characteristics of metal-hydrogen bonds in coordination complexes. Ligand effects on metal-hydrogen bonding were studied.
Color poster with graphs, diagrams, images, and tables.
Keywords: Ligands (Biochemistry); Transition metal hydrides; Hydrogen bonding--Research; Posters